Effect of Micronutrient Application through Seed Coating and Foliar Spraying on Growth and Seed Yield of Pigeonpea (Cajanus cajan L.) - MALLIKARJUN G HANDIGANOOR,; S B PATIL,; SN VASUDEVAN,; SR DODDAGOUDAR,; PH KUCHANUR, (Seed Research, 2026)
An experiment was conducted at Main Agricultural Research Station, University of Agricultural Sciences, Raichur to investigate the effect of micronutrient application as seed coating s and foliar spray, on growth and seed yield of pigeonpea during kharif 2014. The results revealed that among the different treatments seed polymer coating (6 ml/kg of seed) with potassium molybdate + ZnSO4 + boron (each @2g / kg of seed) along with two foliar sprays of potassium molybdate (0.1%) + zinc sulphate (0.5%) in EDTA form + borax (0.2%) at an interval of 10 days during flowering stage recorded significantly higher plant height, leaf area index, chlorophyll content, stomatal conductance and resistance, effective root nodules per plant, number of branches per plant, number of pods per plant, number of seeds per pod and seed yield as compared to control.